Kepastian Hukum bagi Warga Negara melalui Peran Pejabat Umum dalam Sistem Ketatanegaraan Indonesia : Legal Certainty for Citizens through the Role of Public Officials in the Indonesian Constitutional System - Abdul Jafar; Yonani; Heni Marlina; Syamsul; Sarah (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This study aims to analyze the position of public officials within the Indonesian constitutional system and to examine the consistency of regulations governing their authority in ensuring legal certainty for citizens. This research employs a normative juridical approach using statutory, conceptual, and limited case approaches. The primary legal materials include the 1945 Constitution of the Republic of Indonesia, Law Number 30 of 2004 on the Office of Notary, and Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. The findings indicate that constitutionally, public officials function as state instruments exercising public authority to ensure legal certainty. However, the regulation of public officials’ authority across various sectoral laws remains fragmented and potentially creates legal uncertainty. Therefore, regulatory harmonization and strengthened oversight mechanisms are essential to ensure that public officials effectively protect citizens’ constitutional rights within Indonesia’s rule of law framework.